Orchid blues - Woods, Stuart (Woods, Stuart. Holly Barker novel., 2001)
Holly is on her way to be married to Jackson Oxenhandler, her steady beau, when her wedding day is shattered by a serious crime that takes place very close to home. A highly disciplined team of men hit a bank in Orchid Beach, Florida, and the waves from this robbery nearly capsize Holly's life. She vows to find these men-who have been careful enough to leave nothing behind except the corpse of a bank customer-and quickly, she discovers evidence that leads her into the midst of what appears to be a politically motivated clan. Her father, Ham, a retired army chief master sergeant, is her ticket into this strange world, and what Ham inds there stuns both Holly and her FBI contact, Harry Crisp. Holly and Ham find themselves sucked into a whirlpool of crazed criminality and, in the end, the FBI can do little to help them. This time, Holly, Ham, and Daisy are on their own, and they wouldn't have it any other way.